2016
DOI: 10.1016/j.pjnns.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of blink reflex in multisystem atrophy, progressive supranuclear palsy and Parkinson disease

Abstract: The most frequently abnormal blink reflexes, comparing the MSA, PSP and PD groups, were present in PD patients. We postulate that this may be explained by pathological influence of nigrostriatal pathway on the circuit linking the basal ganglia, cerebellum and brainstem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Our study indicates that an abnormal BR is common in patients with WD. Several reports suggest that BR may be abnormal in patients with some neurodegenerative disorders with various etiology and localization of lesions (Yavuz et al 2015 ; Szmidt-Salkowska et al 2016 ; de Tommaso et al 2001 ; Valls-Solé et al 2004 ). Patients with dementia with Lewy bodies (DLB) have also been reported to have abnormalities in BR (Anzellotti et al 2008 ; Bonanni et al 2007 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study indicates that an abnormal BR is common in patients with WD. Several reports suggest that BR may be abnormal in patients with some neurodegenerative disorders with various etiology and localization of lesions (Yavuz et al 2015 ; Szmidt-Salkowska et al 2016 ; de Tommaso et al 2001 ; Valls-Solé et al 2004 ). Patients with dementia with Lewy bodies (DLB) have also been reported to have abnormalities in BR (Anzellotti et al 2008 ; Bonanni et al 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of studies conducted with patients with Parkinson’s disease (Yavuz et al 2015 ; Szmidt-Salkowska et al 2016 ), multisystem atrophy (MSA), progressive supranuclear palsy (PSP) (Szmidt-Salkowska et al 2016 ) and Huntington’s disease (de Tommaso et al 2001 ; Valls-Solé et al 2004 ), it may be assumed that abnormal BR will be observed in some patients with WD. Abnormal BR results can be caused by abnormalities in the cerebral cortex and in the basal ganglia (Esteban 1999 ), both of which are seen in WD.…”
Section: Introductionmentioning
confidence: 99%
“…Previous neurophysiological studies evaluated R2BRRC in PD and APs showing that PD patients exhibited increased brainstem excitability (Kimura 1973 ; Sciacca et al 2020a ); furthermore, an asymmetrical EMG activity with increase of blink reflex components on the LAS compared to MAS has been observed in PD patients (Dengler et al 1982 ) together with the presence of a higher AI of R2BRRC differentiating PD from PSP and MSA patients (Sciacca et al 2020a ). Concerning APs, only a few studies investigated brainstem excitability by the application of blink reflex and R2BRRC (Sciacca et al 2020a , b ; Sciacca et al 2018 ; Valls-Solé et al 1997 ; Szmidt-Salkowska et al 2016 ) showing that PSP and MSA patients exhibited an increased brainstem excitability compared to CBS patients. In this study, we added and confirmed previous data showing that PD and CBS patients at the early stages of disease presented an inverse pattern of brainstem excitability, with PD patients showing an increased excitability in LAS compared to MAS and a higher AI of R2BRRC, whereas CBS group did not show any differences between LAS and MAS excitability.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only a few studies have been conducted on BR and BR recovery cycle in atypical parkinsonian syndromes [4,11,12]. Kiziltan and colleagues evaluated the BR and trigeminocervical reflex in patients with primary progressive freezing of gait and PSP with freezing of gait, observing an increased excitability of trigeminocervical circuits in primary progressive freezing of gait [11].…”
Section: Discussionmentioning
confidence: 99%
“…Kiziltan and colleagues evaluated the BR and trigeminocervical reflex in patients with primary progressive freezing of gait and PSP with freezing of gait, observing an increased excitability of trigeminocervical circuits in primary progressive freezing of gait [11]. Szmidt-Salkowska and colleagues noted significant differences in R2 latencies of BR in Parkinson's disease compared with multisystem atrophy and PSP [12]. Valls-Sol e and colleagues evaluated facial reflex responses, BR and R2BRRC in Parkinson's disease, multisystem atrophy, PSP and CBS [4].…”
Section: Discussionmentioning
confidence: 99%